POTENSI EKSTRAK BUNGA PISANG KEPOK (MUSA PARADISIACA L.) SEBAGAI ANTIOKSIDAN DENGAN METODE DPPH (1,1-DIFENIL-2-PIKRILHIDRAZIL) - Farisya Nurhaeni; Amelia Handayani Burhan; Fydika Nurul Riani Sumarjo; Aditya Fitriasari (Institut Kesehatan dan Teknologi Al Insyirah, 2025)
Kepok banana flower has potential as an antioxidant so it can inhibit free radical activity. Previous research stated that banana flower extract (Musa acuminate) has an IC50 value of 13.21 µg/ml, which means it has very strong antioxidant activity. Therefore, a study was carried out to fractionate the ethanol extract of kepok banana flowers and determine the antioxidant activity of each of these fractions. It is hoped that with this research a purer fraction will be obtained to increase the antioxidant activity. Extraction was carried out by maceration using 96% ethanol, while fractionation was carried out by chloroform. Testing the antioxidant activity using the DPPH method with UV-VIS spectrophotometry. The wavelength used is 517 nm. Extraction was carried out on 30 grams of kepok banana flower powder with 96% ethanol solvent so that 1.27 grams of the thick extract was obtained. Fractionation was carried out on 500 mg of ethanol extract from kepok banana flowers which produced 0.21 gram of soluble fraction and 0.28 gram of chloroform insoluble fraction. The results showed that the IC50 values of ethanol extract, soluble fraction and chloroform insoluble fraction of kepok banana flower extract were 26.00 µg/ml, 236.17 µg/ml, and 18.70 µg/ml respectively. It can be concluded that the ethanol extract and chloroform insoluble fraction of kepok banana flowers have very strong antioxidant activity, while the chloroform soluble fraction has weak antioxidant activity.